Effect of Ammonium Carbonate Salt Concentration on Structural and Ionic Conductivity of Cellulose Based Solid Polymer Electrolytes - M. I. H. Sohaimy; M. I. N. Isa (Springer, 2024)
The cellulose based solid polymer electrolytes (SPEs) containing carboxymethyl cellulose doped with ammonium carbonate (AC) have been prepared via solution casting techniques. The XRD analysis shows that the SPE films are amorphous in nature. FTIR spectroscopy shows that the occurrence of interaction between AC salt and the polymer matrix at wavenumber range of 800-1800 cm-1. Impedance measurement shows that the highest ionic conductivity was achieved at 7.71×10−6 S cm−1 (7 wt% AC) obtained at 303 K. The ionic conductivity of SPE films at different salt concentration were revealed to follow Arrhenius law and thermally assisted.